Synthesis of pyrrolidinedione-fused hexahydropyrrolo[2,1-a]isoquinolines via three-component [3 + 2] cycloaddition followed by one-pot N-allylation and intramolecular Heck reactions - Ma, Xiaoming; Meng, Suzhi; Zhang, Xiaofeng; Zhang, Qiang; Yan, Shenghu; Zhang, Yue; Zhang, Wei (Beilstein Journal of Organic Chemistry, 2020)
Two kinds of [3 + 2] cycloaddition intermediates generated from the three-component reactions of 2-bromobenzaldehydes and maleimides with amino esters or amino acids were used for a one-pot N-allylation and intramolecular Heck reactions to form pyrrolidinedione-fused hexahydropyrrolo[2,1-a]isoquinolines. The multicomponent reaction was combined with one-pot reactions to make a synthetic method with good pot, atom and step economy. MeCN was used as a preferable green solvent for the reactions.
Keywords: [3 + 2] cycloaddition; Heck reaction; hexahydropyrrolo[2,1-a]isoquinoline; one-pot reactions

The Alkaloids: Chemistry and Biology - Pässler, U.; Knöller, H. J. (The pyrrolo[2,1-a]isoquinoline alkaloids, 2011)

(untitled) - Fan, H.; Peng, J.; Hamann, M. T.; Hu, J.-F. (Chem. Rev., 2008)

(untitled) - Zhang, Q.; Tu, G.; Zhao, Y.; Cheng, T. (Tetrahedron, 2002)

(untitled) - Zhang, F.; Simpkins, N. S.; Blake, A. J. (Org. Biomol. Chem., 2009)

The Alkaloids: Chemistry and Biology - Parsons, A. F.; Palframan, M. J. (Erythrina and related alkaloids, 2010)

(untitled) - Andersen, R. J.; Faulkner, D. J.; He, C. H.; Van Duyne, G. D.; Clardy, J. (J. Am. Chem. Soc., 1985)

(untitled) - Reddy, M. V. R.; Rao, M. R.; Rhodes, D.; Hansen, M. S. T.; Rubins, K.; Bushman, F. D.; Venkateswarlu, Y.; Faulkner, D. J. (J. Med. Chem., 1999)

(untitled) - Malla Reddy, S.; Srinivasulu, M.; Satyanarayana, N.; Kondapi, A. K.; Venkateswarlu, Y. (Tetrahedron, 2005)

(untitled) - Wang, R.-F.; Yang, X.-W.; Ma, C. M.; Cai, S.-Q.; Li, J.-N.; Shoyama, Y. (Heterocycles, 2004)

(untitled) - Yang, Z.; Liu, C.; Xiang, L.; Zheng, Y. (Phytother. Res., 2009)

(untitled) - Lin, W.; Ma, S. (Org. Chem. Front., 2017)

(untitled) - Umihara, H.; Yoshino, T.; Shimokawa, J.; Kitamura, M.; Fukuyama, T. (Angew. Chem., Int. Ed., 2016)

(untitled) - Komatsubara, M.; Umeki, T.; Fukuda, T.; Iwao, M. (J. Org. Chem., 2014)

(untitled) - Kapat, A.; Kumar, P. S.; Baskaran, S. (Beilstein J. Org. Chem., 2007)

(untitled) - Dondas, H. A.; Fishwick, C. W. G.; Gai, X.; Grigg, R.; Kilner, C.; Dumrongchai, N.; Kongkathip, B.; Kongkathip, N.; Polysuk, C.; Sridharan, V. (Angew. Chem., Int. Ed., 2005)

(untitled) - Sun, H.; Tawa, G.; Wallqvist, A. (Drug Discovery Today, 2012)

(untitled) - Hu, Y.; Stumpfe, D.; Bajorath, J. (J. Med. Chem., 2017)

(untitled) - Zhi, S.; Ma, X.; Zhang, W. (Org. Biomol. Chem., 2019)

(untitled) - Haji, M. (Beilstein J. Org. Chem., 2016)

(untitled) - Dömling, A.; Wang, W.; Wang, K. (Chem. Rev., 2012)

(untitled) - Pandey, G.; Banerjee, P.; Gadre, S. R. (Chem. Rev., 2006)

(untitled) - Hashimoto, T.; Maruoka, K. (Chem. Rev., 2015)

(untitled) - Amornraksa, K.; Grigg, R.; Gunaratne, H. Q. N.; Kemp, J.; Sridharan, V. (J. Chem. Soc., Perkin Trans. 1, 1987)

(untitled) - Coldham, I.; Hufton, R. (Chem. Rev., 2005)

(untitled) - Harju, K.; Yli-Kauhaluoma, J. (Mol. Diversity, 2005)

(untitled) - Zhang, W.; Zhang, X.; Ma, X.; Zhang, W. (Tetrahedron Lett., 2018)

(untitled) - Tsuge, O.; Kanemasa, S.; Ohe, M.; Takenaka, S. (Bull. Chem. Soc. Jpn., 1987)

(untitled) - Grigg, R.; Idle, J.; McMeekin, P.; Vipond, D. (J. Chem. Soc., Chem. Commun., 1987)

(untitled) - Grigg, R.; Surendrakumar, S.; Thianpatanagul, S.; Vipond, D. (J. Chem. Soc., Perkin Trans. 1, 1988)

(untitled) - Ma, X.; Zhang, X.; Xie, G.; Awad, J. M.; Zhang, W. (Tetrahedron Lett., 2019)

(untitled) - Zhang, W.; Lu, Y.; Hiu-Tung Chen, C.; Zeng, L.; Kassel, D. B. (J. Comb. Chem., 2006)

(untitled) - Lu, Q.; Huang, X.; Song, G.; Sun, C.-M.; Jasinski, J. P.; Keeley, A. C.; Zhang, W. (ACS Comb. Sci., 2013)

(untitled) - Ma, X.; Zhang, X.; Awad, J. M.; Xie, G.; Qiu, W.; Zhang, W. (Green Chem., 2019)

(untitled) - Muthengi, A.; Zhang, X.; Dhawan, G.; Zhang, W.; Corsini, F.; Zhang, W. (Green Chem., 2018)

(untitled) - Zhang, X.; Qiu, W.; Ma, X.; Evans, J.; Kaur, M.; Jasinski, J. P.; Zhang, W. (J. Org. Chem., 2018)

(untitled) - Ma, X.; Zhang, X.; Awad, J. M.; Xie, G.; Qiu, W.; Muriph, R. E.; Zhang, W. (Tetrahedron Lett., 2020)

(untitled) - Ma, X.; Zhang, X.; Qiu, W.; Zhang, W.; Wan, B.; Evans, J.; Zhang, W. (Molecules, 2019)

(untitled) - Zhang, X.; Qiu, W.; Evans, J.; Kaur, M.; Jasinski, J. P.; Zhang, W. (Org. Lett., 2019)

(untitled) - Muthengi, A.; Erickson, J.; Muriph, R. E.; Zhang, W. (J. Org. Chem., 2019)

(untitled) - Grigg, R.; Coulter, T. (Tetrahedron Lett., 1991)

(untitled) - Dumitrascu, F.; Caira, M. R.; Georgescu, E.; Georgescu, F.; Draghici, C.; Popa, M. M. (Heteroat. Chem., 2011)

(untitled) - Boudriga, S.; Haddad, S.; Askri, M.; Soldera, A.; Knorr, M.; Strohmann, C.; Golz, C. (RSC Adv., 2019)

(untitled) - Peng, W.; Zhu, S. (J. Chem. Soc., Perkin Trans. 1, 2001)

(untitled) - An, J.; Yang, Q.-Q.; Wang, Q.; Xiao, W.-J. (Tetrahedron Lett., 2013)

(untitled) - Bastrakov, M. A.; Starosotnikov, A. M. (Russ. Chem. Bull., 2019)

(untitled) - Shang, Y.; Wang, L.; He, X.; Zhang, M. (RSC Adv., 2012)

(untitled) - Dumitrascu, F.; Georgescu, E.; Georgescu, F.; Popa, M. M.; Dumitrescu, D. (Molecules, 2013)

(untitled) - Wu, L.; Sun, J.; Yan, C.-G. (Org. Biomol. Chem., 2012)

(untitled) - Muthusaravanan, S.; Perumal, S.; Yogeeswari, P.; Sriram, D. (Tetrahedron Lett., 2010)

Organic Reactions - Link, J. T. (The intramolecular heck reaction, 2002)

(untitled) - Bharath Kumar Reddy, P.; Ravi, K.; Mahesh, K.; Leelavathi, P. (Tetrahedron Lett., 2018)

(untitled) - Wang, G.; Liu, C.; Li, B.; Wang, Y.; Van Hecke, K.; Van der Eycken, E. V.; Pereshivko, O. P.; Peshkov, V. A. (Tetrahedron, 2017)

(untitled) - Murru, S.; McGough, B.; Srivastava, R. S. (Org. Biomol. Chem., 2014)

(untitled) - Hou, C.; Chen, H.; Xu, X.; Zhu, F.; Guo, L.; Jiang, M.; Yang, C.; Deng, L. (Eur. J. Org. Chem., 2015)

Pot, atom, and Step Economy (PASE) Synthesis - Zhang, W.; Yi, W.-B. (Springer, 2019)

(untitled) - Clarke, P. A.; Santos, S.; Martin, W. H. C. (Green Chem., 2007)